Kinetic Alfvén solitary waves in a plasma with two-temperature superthermal electron populations: the case of Saturn’s magnetosphere - Kourakis, Ioannis (2019)
Thanks to the evidence provided by the Cassini spacecraft mission, it is now established that Saturn’s magnetospheric plasma consists of various types of positive ions, as well as two distinct populations of electrons, at different temperatures. The electron population energy distributions are characterized by long suprathermal tails and have been effectively modelled by kappa-type distributions. Plasma properties are known to vary along the radial direction. A strong magnetic field penetrates the magnetosphere, hence the plasma beta is small, β < 1 for radial distance < 15.2RS (where RS = 60 330 km is the Saturn’s radius). Motivated by these observations, we have investigated the conditions for existence and the dynamics of linear and non-linear kinetic Alfv´en waves (KAWs) in Saturn’s magnetosphere. We have considered a low-β (stronglymagnetized) plasma, comprising of positive ions and two electron populations (‘cold’ and ‘hot’) characterized by non-Maxwellian (kappa) distributions. In the small-amplitude regime, harmonic analysis leads to a linear dispersion relation bearing explicit dependence on the characteristics of the suprathermal components. In the nonlinear regime, large-amplitude stationary profile kinetic Alfv´en solitary wave solutions are obtained via a two-component pseudopotential method, associated with either positive or negative potential structures (pulses) propagating at sub- and super-Alfv´enic speeds, respectively. The effect of various intrinsic plasma configuration properties (hot-to-cold electron density and temperature ratio; superthermality indices κc and κh; plasma beta) as well as propagation parameters (pulse speed, direction of propagation) on the characteristics of KAW solitary waves are discussed